In-line coupling of supported liquid membrane extraction to capillary electrophoresis for simultaneous analysis of basic and acidic drugs in urine - Pantůčková, Pavla; Kubáň, Pavel (Journal of chromatography. A, 2017)
Simultaneous extraction of basic and acidic drugs across thin supported liquid membrane (SLM) and direct injection of the extracted drugs from SLM surface into capillary electrophoresis (CE) were demonstrated. A microextraction device compatible with injection system of commercial CE instrument was filled with 20μL of sample and 10μL of acceptor solution, which were interspaced by the SLM impregnated with 5μL of organic solvent. Extractions of three basic drugs (nortriptyline, haloperidol and loperamide) and two acidic drugs (ketoprofen and naproxen) were achieved at optimized conditions including 1-ethyl-2-nitrobenzene as SLM solvent, natural pH of sample solution, 2.5mM NaOH acceptor solution and 30min extraction time. The extracted drugs were directly injected into CE for separation and quantification in a background electrolyte solution consisting of 30mM ammonium acetate adjusted to pH 4.2 with acetic acid. The entire analytical procedure including drugs extraction, injection, separation and quantification was automated in the CE instrument and the only manual procedures were SLM impregnation and filling the microextraction device with sample and acceptor solutions. The analytical method was suitable for simultaneous determination of basic and acidic drugs in undiluted human urine samples and was used for direct determination of naproxen in urine after oral administration of Nalgesin S tablet. Efficient elimination of sample matrix and selective transfer of basic and acidic drugs were achieved and the hyphenated SLM-CE method was characterized by repeatability of peak areas ranging from 3.7 to 13.4%, linear relationship between peak areas and concentrations (r2=0.994-0.999) and limits of detection between 0.05 and 1.5μg/mL.
Keywords: Supported liquid membrane; Capillary electrophoresis; Sample treatment; Electrophoresis, Capillary; Simultaneous extraction; elektroforéza kapilární; Reproducibility of Results; Urinalysis; lidé; Nitrobenzenes; Pharmaceutical Preparations; léčivé přípravky; reprodukovatelnost výsledků; limita detekce; analýza moči; Limit of Detection; Complex samples; nitrobenzeny; Naproxen; naproxen; Humans